The effectiveness of programmable logic controller teaching aids for control system module in vocational college - Yahaya, Muhammad Hazziq; Mustafa, Mohamad Zaid; Ahad, Rosnee (Horizon Research Publishing, 2019)
Teaching aids are important in the process of teaching and learning. The use of teaching aids in teaching and learning process is necessary for teachers to ensure the delivery of information related to the subjects taught is more visible and systematic, so it can be followed by students. This study aims to develop a programmable logic controller learning kit as a teaching aid to enhance the understanding of students in the control system module in a vocational college. This study implemented a quasi-experimental approach, involving two groups of fourth year students in vocational colleges that are enrolled in the control system module. A total of 60 respondents were randomly selected in cluster - 30 respondents from each vocational college. A pre-test and a post-test were conducted to assess the students’ level of understanding on programmable logic controller topic. The pre-test and post-test have three parts which cover objective questions and subjective questions to ensure the similarity on the level of knowledge among respondents. The pre and post-test have the same question, but they were differentiated by the position of the question. A post-test will be given after the treatment and from the results, and the difference between the impact of the effective use of conventional method and the use of developed kit was analysed. Then, the questionnaires were distributed to 30 respondents to assess the effectiveness of the kit. The questionnaire covers three main aspects to be assessed. This learning kit can help teachers at vocational colleges to increase understanding and the knowledge of students on programmable logic controller topic in control system module. At the end of this study, the results have shown a positive effect on students' understanding of programmable logic controller topic. In addition, it can improve students’ achievement in control system module in a vocational college.